Pengembangan Aplikasi Android untuk Latihan Fisik dimasa Pandemi berdasarkan Cuaca - Ikhsanul Isra Yunelfi; Ratih Kartika Dewi; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic changed the world in a short time, spreading rapidly on a wide scale and causing many fatalities. The Bureau of Meteorology, Climatology and Geophysics (BMKG) predicts that almost all regions of Indonesia will enter the transision period season. In the midst of the coronavirus pandemic, with these extreme weather changes, it is recommended that people stay at home, maintain a clean and healthy lifestyle, exercise diligently. Exercise is important for body fitness, but excessive exercise actually decreases immunity. That's why many athletes are more susceptible to Covid-19. With the development of this app, users get a type of sports recommendation that suits the weather conditions.This Android-based Weather-based Sports Recommendation System during a Pandemic is designed with FITT principles which is a great way to monitor exercise programs. The system will detect the location and weather around the user and provide sports recommendations according to FITT's advice and principles. Functional testing of applications is conducted in the blackbox method by obtaining a valid 100% value, and non-functional testing is conducted in sus method with a value of 74.5 which is well categorized and has a Grade B..